Effects of temperature and photoperiod on growth, physiological, and behavioral performance in steelhead trout (Oncorhynchus mykiss) under indoor aquaculture condition - Ma, Zhen; Zhang, Jia; Zhang, Xu; Li, Haixia; Liu, Ying; Gao, Lei (Frontiers in Marine Science, 2023)
Light and temperature are necessary conditions for migratory fish. The assessment of fish physiology and behavior is important for identifying fish welfare, but also for the assessment of the optimal setting of recirculating aquaculture systems (RASs). This study aimed to explore the interactive effect of photoperiod and temperature on steelhead trout culture. Four treatments were set up with specific settings were as follows: a LP-LT group treated with 16L:8D and 12℃, a LP-HT group treated with 16L:8D and 16℃, a SP-LT group treated with 12L:12D and 12℃, and a SP-HT group treated with 12L:12D and 16℃. Two indexes, locomotor activity and social interaction, were used for behavioral analysis. The growth performances were significantly lower in treatments LP-LT and SP-LT. The treatment LP-HT had significantly higher growth performance than the other treatments, but no significant differences were noted in survival rate and coefficient of variation. The results of the physiological parameters showed that the recovery time from stress varied among different treatments. After 60 days of the experiment, superoxide dismutase and alanine aminotransferase dropped back to their initial level. The results of Na+-K+-ATPase showed that although the combined effect of photoperiod and temperature could advance the time of smoltification, it may result in poorer salt tolerance. The results of fish behavior indicated that the movement of juveniles should be primarily monitored at higher temperatures or longer photoperiods, and the state parameters should be primarily monitored at lower temperatures or shorter photoperiods. The outcome of this study could provide guidance for the development of effective aquaculture systems.